Analysis Of Dynamic Stability Of Synchronous Generators In Hydro Power Station In The Electrical Energy System In The Matlab Software (Eurasian Journal of Engineering and Technology, 2023)
The article presents the equations of stability of the electric power system, the asynchronous mode and the asynchronous state of the system. A model of the differential equation in the Matlab program is constructed and the necessary results are obtained.